Non-enzymatic portable optical sensors for microcystin-LR. Issue 22 (26th February 2018) - Lvova, Larisa; Guanais Gonçalves, Carla; Prodi, Luca; Lombardo, Marco; Zaccheroni, Nelsi; Viaggiu, Emanuela; Congestri, Roberta; Guzzella, Licia; Pozzoni, Fiorenzo; Di Natale, Corrado; Paolesse, Roberto
Abstract : We report a selective non-enzymatic optical sensor for fast and low-cost detection of microcystin-LR and POCT estimation of water toxicity. Abstract : We present here the development of an all-solid-state optical sensor based on phenyl-substituted diaza-18-crown-6 hydroxyquinoline (DCHQ-Ph) for the indirect selective detection of microcystin-LR (MC-LR), reaching a very low detection limit of 0.05 μg L −1, well below the World Health Organisation (WHO) guideline value (1 μg L −1 ) in potable water. We demonstrate the potential applicability of the developed method in fast and low-cost water toxicity estimation.